The effect of product quality and service quality on Indihome customer loyalty at Witel Tangerang - Wahyudin (Privietlab, 2021)
This study aims to determine how much influence product quality and service quality have on customer loyalty at Indihome Witel Tangerang. The population in this study is Indihome customers who are in Witel Tangerang. The sample in this study amounted to 100 customers, with the technique of determining the sample using nonprobability sampling and the sampling technique using accidental sampling, namely by distributing questionnaires to Indihome customers in Witel Tangerang. The results of data processing show that product quality and service quality partially affect customer loyalty Indihome witel Tangerang, this is indicated by t-count product quality 4.714 with a significant level of 0.000 and t-count Price 13,491 with a significant level of 0.000, the data above shows that the value of t-count is greater than t table 1.660 and the significant value of the two variables is below 0.05, then product quality and service quality have a very strong influence on customer loyalty which is indicated by the coefficient of determination which indicates the R2 value is 80.8%